Factors Associated with High Rates of Caesarean Deliveries: A Cross Sectional Study Classifying Deliveries According to Robson in Mengo Hospital Kampala - Nantume, Susan; Baluku, Eric Murungi; Kwesiga, Doris; Waiswa, Peter (Risk Management and Healthcare Policy, 2023)
Introduction: The number of caesarean section (CS) continues to rise worldwide. CS can improve outcomes in infants and mothers. However, if used improperly, the potential harm can outweigh the potential benefits. Aim: The study was to determine the factors associated with high cesarean section rates at Mengo Hospital. Methods: This cross-sectional study used a mixed-method approach that included a retrospective review of 1276 casebooks using the Robson Ten Group Classification System (RTGCS) for births that occurred at Mengo Hospital in December 2018, January, and February 2019. Questionnaire was used for data collection from 200 mothers on second day after birth from 24th May to 19th July 2019. Eight key informants were interviewed within the same period. Quantitative data were analyzed using STATA V.14, thematic analysis for qualitative data. Univariate, bivariate, and multivariate analyses were performed to determine the association between predisposing factors and outcome variables using chi-square and modified Poisson. Results: Caesarean section rate (CSR) from casebooks was 49% and 64% from the primary data. Group 5(Previous CS, single cephalic, >37 weeks) had (35.4%) to the total number of cesarean deliveries, followed by Group 1 (Nulliparous, single cesarean deliveries, >37 weeks in spontaneous labour), with 18.4%. Group 3 (ultiparous (excluding previous CS), single cephalic, >37 weeks of spontaneous labor) with (13.7%). The common indications from casebooks were a previous scar (32%), obstructed labor (18%), and previous scar (97.6%). Presence of an obstetric indication, influence of husband, friends, relatives, and mother’s desire for a CS were closely associated with caesarean delivery. Mothers said that occurrence of CS was due to health workers reducing the stress of monitoring labour and financial benefits from CS deliveries by the hospital. Conclusion: Repeat CS made the highest CSR contribution; therefore, strategies to reduce the frequency of the procedure should include avoiding medically unnecessary primary CS and encouraging vaginal birth after previous CS where applicable.
Keywords: Robson Ten Group Classification System; Cesarean section; Previous scar